Pengembangan Kurikulum Pesantren Muadalah - Fachru Abdul Rahman; Ika Kartika (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
The regulations for the development of the muadalah Islamic boarding school curriculum contained in the Regulation of the Minister of Religion of the Republic of Indonesia number 31 of 2020 emphasize the importance of maintaining the characteristics of each Muadalah Islamic boarding school. development consisting of planning, implementation and evaluation is a crucial aspect in this process. This research method uses a qualitative approach with triangulation data collection techniques. The research location is at the Rafah Islamic Boarding School. The results of this research indicate that the development of the Islamic boarding school curriculum at the Rafah Islamic Boarding School focuses on planning, implementation and evaluation. Planning for the curriculum Development of the Muadalah Islamic Boarding School refers to the vision and mission of the Rafah Islamic Boarding School by enriching the curriculum content that integrates science, faith and charity. There is close integration between religious knowledge and general science in the curriculum, which is designed in intra-curricular, extra-curricular and co-curricular contexts. Implementation of Islamic Boarding School Curriculum Development begins with the curriculum orientation stage for the teachers who handle the material. The muadalah curriculum program was developed by adopting a learning process inside and outside the classroom, which reflects the characteristics of the Rafah Islamic Boarding School education system which is integrative, comprehensive and independent. Curriculum Development Evaluation involves supervision activities which include guarding, supervising and controlling curriculum implementation.